2016
DOI: 10.1002/ps.4298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atrazine prohibition on the sustainability of weed management in Wisconsin maize production

Abstract: The results indicate that prohibiting atrazine reduced the diversity of weed management practices, which increased the risk of herbicide resistance. Our concern is that a regulatory policy to address one issue (atrazine in groundwater) has induced farmer responses that increase problems with another issue (herbicide-resistant weeds) that longer term will contribute to water quality problems from increased soil erosion and offset the initial benefits. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…An assessment of atrazine use for corn production in Wisconsin examined what impact atrazine use restrictions had on the range of weed management practices. 27 A survey of farmers was done to gather data from both areas where atrazine restrictions had been implemented and areas that had no restrictions. The results found that restricting the use of atrazine increased the adoption of herbicide tolerant (HT) corn varieties, which then contributed to an increase of conservation tillage practices.…”
Section: Insights From the Literature On The Role Of Agricultural Bio...mentioning
confidence: 99%
“…An assessment of atrazine use for corn production in Wisconsin examined what impact atrazine use restrictions had on the range of weed management practices. 27 A survey of farmers was done to gather data from both areas where atrazine restrictions had been implemented and areas that had no restrictions. The results found that restricting the use of atrazine increased the adoption of herbicide tolerant (HT) corn varieties, which then contributed to an increase of conservation tillage practices.…”
Section: Insights From the Literature On The Role Of Agricultural Bio...mentioning
confidence: 99%
“…HT seeds do not directly cause the development of herbicide resistant weeds, as herbicide resistant weeds have evolved in regions such as Western Australia where HT crops are not used [42]. Rather, HT crops contribute by encouraging farmers to rely on fewer herbicides modes of action and less tillage, which accelerate the development and spread of resistant weed populations [43,44]. Problems with herbicide resistant weeds continue to develop and spread globally, which is worrisome because no new herbicide modes of action have become commercially available since the early 1990s…”
Section: Prospects For the Futurementioning
confidence: 99%
“…Weed management is a major challenge in corn production. U.S. corn growers rely primarily on herbicides and tillage for weed management (Dong et al 2017; Grint et al 2022a). Herbicides are the most extensively used pesticide on corn crops, applied to >95% of planted corn hectares in the United States in 2021 (USDA-NASS 2022).…”
Section: Introductionmentioning
confidence: 99%